The implication of neutrophil extracellular traps in nonalcoholic fatty liver disease - Fa, Pengyan; Ke, Benjamin G.; Dupre, Abigail; Tsung, Allan; Zhang, Hongji (Frontiers in Immunology, 2023)
Nonalcoholic fatty liver disease (NAFLD) is an expanding worldwide health concern, and the underlying mechanisms contributing to its progression still need further exploration. Neutrophil extracellular traps (NETs) are intricate formations comprised of nuclear constituents and diverse antimicrobial granules that are released into the extracellular milieu by activated neutrophils upon various triggers, which play a pivotal part in the onset and advancement of NAFLD. NETs actively participate in the genesis of NAFLD by fostering oxidative stress and inflammation, ultimately resulting in hepatic fat accumulation and the escalation of liver injury. Recent insights into the interaction with other hepatic immune populations and mediators, such as macrophages and T regulatory cells, have revealed several important mechanisms that can trigger further liver injury. In conclusion, the formation of NETs emerged as an important factor in the development of NAFLD, offering a promising target for innovative therapeutic approaches against this debilitating condition. This comprehensive review seeks to compile existing studies exploring the involvement of NETs in the genesis of NAFLD and their influence on the immune response throughout the progression of NAFLD.